Impianti produttivi di anfore nella Valle del Volturno durante l’età tardo repubblicana: L’analisi dell’accumulo di Dugenta (Benevento) - Siano, Stefania (Rei Cretariae Romanae Fautorum Acta, 2022)
The kiln-site of Dugenta is located in the territory of Sant’Agata dei Goti (ancient Saticula), a Samnite town on the northwest borders of Campania. The kiln’s location was indicated by the large amount of amphorae fragments scattered on the surface, and the fabric of Dugenta was included in G. Thierrin-Michael’s petrological study of the main Italian production centres for Dressel 1. Nonetheless, the site of the kiln was partially investigated only in the 1997. The paper provides the evaluation of the deposit of amphorae and the pottery assemblage collected during the archaeological excavation, outlining the characteristics of the local production of amphorae and common wares.